2020
DOI: 10.1016/j.jallcom.2020.154201
|View full text |Cite
|
Sign up to set email alerts
|

A Co9S8 microsphere and N-doped carbon nanotube composite host material for lithium-sulfur batteries

Abstract: Lithium-sulfur batteries have emerged as extraordinarily favorable energy storage devices due to their high specific capacity and energy density, safety and low cost. Unfortunately, the wide applications of lithium-sulfur batteries are hampered by several issues, such as the low electronic conductivity and slow redox kinetics, serious volumetric expansion and polysulfide "shuttle effect". To overcome these issues, in our work, we design and synthesize a composite sulfur host material of Co9S8 microspheres and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…[13][14][15][16] However, MoS 2 also has drawbacks such as covering of active sites, poor conductivity, and low OER performance. [17][18][19] In contrast, transition metal sulphides and oxides of Co such as Co 3 S 4 , 20,21 Co 9 S 8 , [22][23][24] Co 4 O 4 , 25 and LaCoO 3 26,27 exhibit higher conductivity and efficient electrocatalytic performance for the OER, but their HER performance is unsatisfactory. Some studies have reported that the electronic structure of MoS 2 can be modulated and optimised by doping with transition metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, MoS 2 also has drawbacks such as covering of active sites, poor conductivity, and low OER performance. [17][18][19] In contrast, transition metal sulphides and oxides of Co such as Co 3 S 4 , 20,21 Co 9 S 8 , [22][23][24] Co 4 O 4 , 25 and LaCoO 3 26,27 exhibit higher conductivity and efficient electrocatalytic performance for the OER, but their HER performance is unsatisfactory. Some studies have reported that the electronic structure of MoS 2 can be modulated and optimised by doping with transition metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…23 While polar materials such as Co 3 O 4 and TiO 2 act as chemical trappers toward LiPSs, they have intrinsically low electrical conductivity, which makes them unable to diffuse/ transform polysulfides in time, leading to a slow redox reaction. 24,25 Therefore, an ideal sulfur carrier should simultaneously realize LiPS adsorption/trapping, which is very critical to achieve an outstanding cycling stability. Currently, transition-metal sulfides (TMSs) have aroused great research interest due to their unique metallic conductivity compared with corresponding metal oxides and appropriate adsorption capacity toward LiPSs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various strategies have been developed to tackle the issues mentioned above. One of the most important strategies focuses on constructing various composites as sulfur host materials, such as carbon materials, , metal oxides, and metal sulfides. Yet, nonpolar carbon exhibits inferior physical adsorption to the polar intermediate polysulfides, which cannot effectively prevent the dissolution of polysulfides . While polar materials such as Co 3 O 4 and TiO 2 act as chemical trappers toward LiPSs, they have intrinsically low electrical conductivity, which makes them unable to diffuse/transform polysulfides in time, leading to a slow redox reaction. , Therefore, an ideal sulfur carrier should simultaneously realize LiPS adsorption/trapping, which is very critical to achieve an outstanding cycling stability. Currently, transition-metal sulfides (TMSs) have aroused great research interest due to their unique metallic conductivity compared with corresponding metal oxides and appropriate adsorption capacity toward LiPSs. , For example, Zhang et al introduced NiS 2 nanoparticles into graphene used as the sulfur host material, which exhibited a high specific capacity of 400 mAh g –1 over 800 cycles at 1 C with almost 98% Coulombic efficiency, benefiting from the chemical adsorption of LiPSs to NiS 2 nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…However, Li-S battery has been firstly hampered by the low electrical conductivity of both sulfur (5 × 10 −30 S cm −1 ) and the discharge product (Li 2 S), which lead to restricting the electron transport and the utilization of the active sulfur [6]. Second, the dissolution of polysulfides in the conventional organic electrolyte (Li 2 S x , 4 ≤ x ≤ 8) provides low coulombic efficiency and short cycle life [7,8]. Third, the volume change of sulfur (about 80%) during the charge-discharge process leads to the pulverization of sulfur cathode and gives up a rapid capacity decay [9,10].…”
Section: Introductionmentioning
confidence: 99%